Neuritis Optik Unilateral sebagai Manifestasi Klinis Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease (MOGAD) - Tannika, Ayudhea; Estiasari, Riwanti; Maharani, Kartika (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Myelin-oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is an oligodendrocytopathic autoimmune disorder, characterized by demyelination and inflammation in the central nervous system, especially brain parenchyma and spinal cord. There are three main clinical manifestations in MOGAD: optic neuritis, transverse myelitis, and acute disseminated encephalomyelitis (ADEM). This case report presents a seropositive anti-MOG patient with early manifestation of optic neuritis. A 29 years old man presented with a complaint of blurry right vision and dull pain around his right eye in the last 5 months before hospital admission. Neurological examination revealed a right visual acuity of 2/60 and right relative afferent pupillary defect (RAPD). Brain MRI with contrast revealed an enhancement on the right optic nerve and nonspecific, multiple hyperintense lesions in bilateral frontal and parietal lobes. The patient’s result was reactive for anti-MOG antibody. After the administration of high dose methylprednisolone (1000 mg) for 5 consecutive days, the patient’s visual acuity was slowly improving; supported with an improvement on the Humphrey visual field analyzer. Immunosuppressant agent azathioprine was given as a long-term treatment without any worsening symptoms to this day. Unilateral optic neuritis could be an early clinical manifestation in MOGAD. It is important for clinicians to identify typical and atypical optic neuritis to be able to determine follow-through examination and workup and the associated differential diagnosis. Optic neuritis in MOGAD could be improved by the administration of high dose methylprednisolone, along with immunosuppressant therapy as long-term therapy